Cancer surviving patients' rehabilitation - understanding failure through application of theoretical perspectives from Habermas - Jensen Anders B; Soendergaard Jens; Mikkelsen Thorbjørn H; Olesen Frede (BMC, 2008)
Abstract This study aims to analyze whether the rehabilitation of cancer surviving patients (CSPs) can be better organized. The data for this paper consists of focus group interviews (FGIs) with CSPs, general practitioners (GPs) and hospital physicians. The analysis draws on the theoretical framework of Jürgen Habermas, utilizing his notions of 'the system and the life world' and 'communicative and strategic action'. In Habermas' terminology, the social security system and the healthcare system are subsystems that belong to what he calls the 'system', where actions are based on strategic actions activated by the means of media such as money and power which provide the basis for other actors' actions. The social life, on the other hand, in Habermas' terminology, belongs to what he calls the 'life world', where communicative action is based on consensual coordination among individuals. Our material suggests that, within the hospital world, the strategic actions related to diagnosis, treatment and cure in the biomedical discourse dominate. They function as inclusion/exclusion criteria for further treatment. However, the GPs appear to accept the CSPs' previous cancer diagnosis as a precondition sufficient for providing assistance. Although the GPs use the biomedical discourse and often give biomedical examples to exemplify rehabilitation needs, they find psychosocial aspects, so-called lifeworld aspects, to be an important component of their job when helping CSPs. In this way, they appear more open to communicative action in relation to the CSPs' lifeworld than do the hospital physicians. Our data also suggests that the CSPs' lifeworld can be partly colonized by the system during hospitalization, making it difficult for CSPs when they are discharged at the end of treatment. This situation seems to be crucial to our understanding of why CSPs often feel left in limbo after discharge. We conclude that the distinction between the system and the lifeworld and the implications of a possible colonization during hospitalization offers an important theoretical framework for determining and addressing different types of rehabilitation needs.